2013
DOI: 10.1542/peds.2012-2996
|View full text |Cite
|
Sign up to set email alerts
|

Screening Examination of Premature Infants for Retinopathy of Prematurity

Abstract: This statement revises a previous statement on screening of preterm infants for retinopathy of prematurity (ROP) that was published in 2006. ROP is a pathologic process that occurs only in immature retinal tissue and can progress to a tractional retinal detachment, which can result in functional or complete blindness. Use of peripheral retinal ablative therapy by using laser photocoagulation for nearly 2 decades has resulted in a high probability of markedly decreasing the incidence of this poor visual outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
257
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 513 publications
(260 citation statements)
references
References 22 publications
(8 reference statements)
1
257
0
2
Order By: Relevance
“…Intravitreal anti-VEGF therapy has been increasingly used in severe ROP cases; hence, whether or not the systemic leakage of anti-VEGF can cause any short-or longterm adverse effects on the tissues or organs has always been an issue (10)(11)(12)(13)(14). The effects of this therapy on other tissues, including the lungs, were not investigated thoroughly in the present study, although we have previously reported a better systemic clinical course of BPD in preterm babies after the injection of IVB (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravitreal anti-VEGF therapy has been increasingly used in severe ROP cases; hence, whether or not the systemic leakage of anti-VEGF can cause any short-or longterm adverse effects on the tissues or organs has always been an issue (10)(11)(12)(13)(14). The effects of this therapy on other tissues, including the lungs, were not investigated thoroughly in the present study, although we have previously reported a better systemic clinical course of BPD in preterm babies after the injection of IVB (10).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in recent years a new treatment modality involving the intravitreal injection of anti-VEGF (vascular endothelial growth factor) agents (intravitreal bevacizumab (IVB)) has been used in the treatment of ROP with high success rates of up to 100% in even the most aggressive forms of the disease (10)(11)(12)(13)(14). However, anti-VEGF agents can gain access to the systemic circulation following an intravitreal injection (15)(16)(17)(18)(19), and the systemic adverse effects of intravitreal anti-VEGF agents have always been a concern.…”
Section: Introductionmentioning
confidence: 99%
“…ROP is a leading cause of blindness in kids. Doctors recommend that pre-term babies that are born earlier than 30 weeks or weigh less than 1,500 g at birth should have eye exams to monitor how the blood vessels in the eyes are growing [3].…”
Section: Cerebral Palsymentioning
confidence: 99%
“…Effective care now requires that at-risk infants receive carefully timed retinal examinations by an ophthalmologist who is experienced in the examination of preterm infants for ROP on a scheduled basis according to their gestational age at birth and their subsequent disease severity and that all pediatricians who care for these at-risk preterm infants be aware of this schedule. 21 Because unchecked ROP can lead to permanent blindness, it is important that all infants be screened in a timely fashion, recognizing that not all infants require treatment. It is important to recognize that screening parameters vary in countries across the globe.…”
Section: Screening For Ropmentioning
confidence: 99%
“…Follow up exams are recommended on the basis of retinal findings as per the international classification and the schedule is outlined by the AAP. 21 5. Plus disease is defined as abnormal dilation and tortuosity of the posterior retinal blood vessels in 2 or more quadrants of the retina in zones I or II.…”
Section: Infants With a Birth Weight Of ≤1500 Grams Or Ga≤30mentioning
confidence: 99%